Preparation of Cellulose Sulphate and Evaluation of its Properties (Journal of Fiber Bioengineering and Informatics, 2018)
This paper reports the reaction of cotton cellulose with sulphamic acid using pad bake process. FT-IR and FT-Raman were used to analyse the intermediate products formed during this study. The self-crosslinking of the modified cotton fibre has special characteristics including good dye ability in case of ammonia or ethanolamine initiated crosslinking. Peroxide should react with the modified fibre to give peroxy cellulose. The self bleaching and anti-bacterial qualities of this reacted cellulose are worthy of investigation.
Keywords: Cotton cellulose; sulphamic acid; self-crosslinking; self bleaching; anti-bacterial